Modeling the catalytic effect of transition metal complexes in water oxidation and hetero-diels-alder reactions - Avcı, Öyküm Naz. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2019., 2019)
This dissertation is composed of two parts, the catalytic eﬀect of transition metals on chemical reactions in the ﬁelds of inorganic and organic chemistry has been handled by utilizing Density Functional Theory. In the ﬁrst part, mononuclear ruthenium-based water oxidation catalysts (WOC) and their operative water oxidation mechanisms have been modeled by means of DFT calculations. Computational comparison of the reaction mechanistic cycles for the mononuclear ruthenium based catalysts are investigated in order to understand which factors can aﬀect their reaction pathways and in particular favor one of the two mecha nisms. By taking geometrical and electronic factors into account, the structure/activity relationship has been discussed. In the second part, the eﬀect of transition metal catalysis in inverse electron demand Diels-Alder (IEDDA) reactions, focusing on silver-catalyzed IEDDA reaction of phthalazine and siloxy alkyne, were modeled utilizing DFT calculations. Along with detailed elaboration of proposed operative mechanisms for the silver-catalyzed system, uncatalyzed reaction has been modeled to emphasize the eﬀect of transition metal based catalyst. In addition, the mode of action for the silver-based catalyst as well as its eﬀect on the regioselectivity/speciﬁcity of the reaction have been demonstrated.
Keywords: Water -- Purification -- Oxidation.; Diels-Alder reaction.